2021
DOI: 10.9734/ajaees/2021/v39i1130742
|View full text |Cite
|
Sign up to set email alerts
|

Input Demand and Output Supply Elasticities of Coarse Cereals in India: A Translog Profit and Sure Approach

Abstract: Aims: The aim was to estimate the output supply and input demand elasticities of maize, jowar and bajra production, using the restricted normalised translog profit function, for the major producing states of India (Andhra Pradesh, Maharashtra and Rajasthan).  Study Design: A stratified multi-stage random sampling design was adopted for carrying out the sampling. Place and Duration of Study: The study pertains to cross sectional plot level data for the period 2013-14 and 2017-18. The study is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The positive output price elasticities in this study was similar to the findings of who also reported positive coefficients for output supply in their respective studies (Williamson et al, 2004;Fabiosa et al, 2004;Praduman et al, 2010;Mailena et al, 2013;Macharia et al, 2020;Ashrit, 2021). The coefficient of price elasticity of spent layer in this study which was 1.12 was found to be higher than 0.27 obtained in the study (Maligaya and White, 1989).…”
Section: Elasticities For Own Price and Cross-price Of Poultry Egg Pr...supporting
confidence: 88%
See 1 more Smart Citation
“…The positive output price elasticities in this study was similar to the findings of who also reported positive coefficients for output supply in their respective studies (Williamson et al, 2004;Fabiosa et al, 2004;Praduman et al, 2010;Mailena et al, 2013;Macharia et al, 2020;Ashrit, 2021). The coefficient of price elasticity of spent layer in this study which was 1.12 was found to be higher than 0.27 obtained in the study (Maligaya and White, 1989).…”
Section: Elasticities For Own Price and Cross-price Of Poultry Egg Pr...supporting
confidence: 88%
“…Hence, there is a need to fill this knowledge gap. Though, limited studies were discovered that investigated the responses of factor demand and output supply in agriculture (Maligaya and White, 1989;Shumway and Hongil, 1993;Goyal and Berg, 2003;Fabiosa et al, 2004;Williamson et al, 2004;Rajapaksa and Karunagoda, 2009;Praduman et al, 2010;Geijer et al, 2011;Mailena et al, 2013;Macharia et al, 2020;Ashrit, 2021).…”
Section: Introductionmentioning
confidence: 99%